Towards a self-consistent relativistic model of the exterior gravitational field of rapidly rotating neutron stars - Stute, Matthias; Camenzind, Max (Monthly notices of the Royal Astronomical Society, 2002)
We present a self-consistent, relativistic model of rapidly rotating neutron stars describing their exterior gravitational field. This is achieved by matching the new solution of Einstein's field equations found recently by Manko et al. and the numerical results for the interior of neutron stars with different equations of state calculated earlier by Cook et al. This matching process gives constraints for the choice of the five parameters of the vacuum solution. Then we investigate some properties of the gravitational field of rapidly rotating neutron stars with these fixed parameters.